Studying Variation in Cell Apoptosis Caused by Corticosteroids in Thymus of the Rat - Dustar, Yusef; Hashemi, Mehrdad; Malayeri, Heidar; Ghazi Jahani, Zahra; Neshat Gharamaleki, Mehrdad; Shaveisi Zadeh, Farhad; Karaminia, Ali Asghar; Movafagh, Abolfazl (Asian Pacific Journal of Cancer Biology, 2016)
Background and purpose: Apoptosis or planned death of cells is the main mechanism in completion and hemostasis of mature tissues to terminate useless, contaminated, and mutated/damaged cells through internal suicide pathways. One of the agents that creates apoptosis signals is glucocorticoids. As the representative of corticosteroid drugs, dexamethasone can induce apoptosis via internal endonuclease. Therefore, dexamethasone was used as a synthetic glucocorticoid in rats. The effects of dexamethasone on thymocyte of rats, morphological features of apoptotic cells, and the relationship between drug dosage and severity of apoptosis were examined. Methodology: A treatment group with four subgroups (each with five rats) namely T-a, T-b- T-c, and T-a was formed and received IP dexamethasone of 0.5, 1.5, 2.5, 3.5mg per one-kilogram body weight respectively. In addition, a control group with similar subgroups was formed. Thymus gland of the subjects of both groups was removed six hours after injection. The samples were examined using electron and optical microscopes. Findings: Examinations by optical microscope revealed round or elliptic apoptotic cytoplasmic bodies with or without nucleus basophil materials along with crescentic bodies of chromatin on the apoptotic cells. In addition, electronic microscope images reveled marginal augmentation of nucleus chromatin in osmiophilic forms detached from nucleus fibrillary centers along with a disordered cellular region, endoplasmic reticulum complication, and nucleus fragmentation. There was a direct and significant relationship between the dosage of the drug and the severity of apoptosis. Conclusion and Recommendations: The results showed that standard and higher dosages of corticosteroid stimulated DNA fragmentation in thymocytes and apoptosis of thymocytes induced by corticosteroid is a calcium-depended process.